Towards the construction of a validated numerical system to study the mesoscale dynamics of the North East Atlantic (2003-2006) - Estrada-Allis, Sheila N. (2013)
A detailed validation study has contributed to the construction of a NEAtlantic (NEA), ocean circulation model, for the 2003-2006 period. The comparisons between three model solutions, remote sensing and in situ data, focused on the study of the most dynamical processes of NEA sub-regions. Model validations include (i) comparisons with Sea Surface Temperature (SST), from AVHRR and Microwave-OI; (ii) Eddy Kinetic Energy (EKE), computed from altimetry; (iii) Temperature and Salinity profiles computed from ARGO floats, and (iv) sub-surface temperature, measured in three buoys of Puertos del Estado. Simple statistical methods were used to quantify model-data comparisons. In general, model regional solutions show a good correlation and small Root Mean Squared Error (RMSE) with SST and EKE. The main water masses were well depicted by the regional model; while the region with high salinity values, often dominated by Mediterranean Intermediate Water (MIW), was not accurately resolved. The initial condition and boundary forcing of the regional model was evaluated, particularly concerning the usage of Ocean General Circulation Models (OGCMs), as an alternative to the classical climatological forcing. The analysis of their Kolmogorov energy spectrum determined their effective resolutions and their EKE levels. Mercator global solution at 1/4?, was shown to be an adequate OGCM solution for studying the 2003-2006 period. The energy spectrum analysis also showed that new 1/12? (downscaled), regional solution resolved more energetic scales than the original OGCM, confirming the need to use high spatial resolution regional ocean circulation models to resolve mesoscale and sub-mesoscale phenomena. The regional model (ROMS) was able to reproduce an Iberian Peninsula upwelling event as well as other previously documented NEA processes, such as the westward propagating eddies associated with the Azores Front, with the Canary and with Madeira Archipelagos. The analysis also showed that atmospheric forcing, is important to adequately ...